Inflation and Real Interest Rates on Assets with Different Risk Characteristics: Discussion - Curran, Ward S. (Journal of Finance, 1984)
Ward S. Curran, Inflation and Real Interest Rates on Assets with Different Risk Characteristics: Discussion, The Journal of Finance, Vol. 39, No. 3, Papers and Proceedings, Forty-Second Annual Meeting, American Finance Association, San Francisco, CA, December 28-30, 1983 (Jul., 1984), pp. 712-714